Analisis Id Ego dan Super Ego pada Iklan Televisi Gojek Mempersembahkan: Cerdikiawan - Dani Manesah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study analyzes the representation of the Id, Ego, and Superego in Gojek's television commercial titled "Gojek Presents: Cerdikiawan" using Sigmund Freud's psychoanalytic theory. The study aims to identify how these three components of personality are depicted in the advertisement's narrative and their impact on the audience. The research employs a qualitative case study design, with data collected through observation and content analysis. The results show that the advertisement successfully portrays the conflict between the Id, Ego, and Superego through characters and scenes reflecting primal urges, rational decisions, and moral values. The advertisement also demonstrates how the Ego balances the Id's urges and the Superego's demands, creating an engaging narrative with strong moral messages. This research contributes to theoretical and practical knowledge in film and television studies, particularly in marketing and advertising contexts.